The influence of lithium sulphate on Shannon entropy in lymphocyte chromatin - Jeremić, Marta B; Pantić, Igor V; Jakšić, Mila Z; Pantić, Igor V (Medicinski podmladak, 2018)
Introduction: Lithium affects numerous signal pathways in cells, which may ultimately lead to either increased or decreased gene expression in cell nuclei. However, effects of lithium on higher level of gene organization in the nuclei, like chromatin,  is still poorly understood. Study aim: To investigate the effects of lithium on chromatin organization in the nuclei of lymphocytes by investigating changes in Shannon entropy of chromatin in these cells. Material and Methods: Peripheral blood was treated with lithium sulphate until lithium concentrations of 1mmoL/l, 2 mmoL/l i 3 mmol/l was not reached.  The smears were fixed with methanol and stained by Felgen method for DNK visualization. Cells in the smear were treated with hydrochloric acid for 120min. Schiff reagent was used for staining for 120min and smear washing was done with 6ml of 10% of water solution of natrium metabisulfite. After staining, digital micrographs for each of the most representative sample of 30 lymphocytic chromatin structures were made. Shannon entropy was calculated by converting micrograph in the format of textual numerical string. Lymphocyte chromatin was also analyzed by textural method analysis. Results: Treatment with 1 mmol/l of lithium sulphate  did not lead to a statistically significant increase in entropy values (p>0.05). However, in samples where the concentration of lithium was 2 i 3 mmol/l, respectively, there was a statistically significant increase in entropy (p